Historisitas dan Dinamika Lembaga Pendidikan Islam di Indonesia - Nasution, Kasron (Al-Fikru: Jurnal Ilmiah, 2020)
This study aims to analyze the historicity and dynamics of Islamic education institutions in Indonesia starting from the classical period, colonialism period, and pre- and post-independence periods. This research uses library research method. Data analysis using analytical descriptive analysis techniques. The results of the study show that Islamic education in Indonesia is the same age as the existence of Islam in the archipelago. Broadly speaking, the history of Islamic educational institutions in Indonesia can be divided into three periods. First, the classical period of the 13th - 16th century, namely since the entry of Islam in Indonesia, the establishment of the Islamic empire, the era of the Islamic empire until the entry of colonizers into Indonesia. Several institutions during this period were mosques, Islamic boarding schools, menasah, rangkang and dayah, surau. Second, the colonial period until the independence period (1600 - 1945). At this time it was divided into two, namely during the Dutch colonial period, there were several institutions namely Elementary Education, Latin Schools, Seminarium Theologicum, Academie der Marine, Chinese Schools. During the Japanese occupation there were several institutions, namely Basic Education (Kokumin Gakko), Advanced Education, consisting of Shoto Chu Gakko, Vocational Education, Higher Education. Third, the period of the independence era (1945-present). There are several institutions, namely pesantren, madrasah, schools, PTKI.